Business Support Policies : Large Spending, Little Impact - Dutz, Mark (World Bank, Washington, DC, 2017)
The focus of this paper is on policies that ought to support productivity, output and employment growth. This support can be direct and indirect, targeted to specific sectors or types of firms or wide ranging. The presence of externalities is the main theoretical justification for deviating from policy neutrality if enhancing economic efficiency is the policy objective. Policies seeking to correct efficiency-related market failures could, for instance, support local within-sector Marshallian externalities or intra-sector spillovers, collective action to overcome sector-specific coordination failures, and the promotion of information spillovers associated with self-discovery and product diversification, based on static or dynamic knowledge, learning or other positive externalities (Harrison and Rodriguez-Clare, 2010). The presence of market failures is only a necessary and not sufficient rationale for government intervention. It is also important to ensure that the benefits to the economy from any intervention outweigh the associated costs including the costs of any government failures in the design and implementation of the intervention - linked among others to imperfect information by government of productivity-related firm needs, government capture and the creation of rents as well as outright corruption (Hevia et al., 2017).